2012
DOI: 10.1016/j.immuni.2011.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of Il17 and Il17f Is Controlled by Conserved Noncoding Sequence 2

Abstract: Summary T helper 17 (Th17) cells specifically transcribe the Il17 and Il17f genes, which are localized in the same chromosome region, but the underlying mechanism is unclear. Here, we report a cis element that we previously named conserved noncoding sequence 2 (CNS2), physically interacted with both Il17 and Il17f gene promoters and was sufficient for regulating their selective transcription in Th17 cells. Targeted deletion of CNS2 resulted in impaired retinoic acid-related orphan receptor gamma (RORγ)-driven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
101
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 38 publications
6
101
0
Order By: Relevance
“…CBP/p300 is thought to be involved at an early stage, consistent with our data showing key sensitivity of human IL 17A transcription to CBP/p300 inhibition (38,39). In murine Th17 cells, conserved noncoding sequence 2 (CNS2) is important to drive Il 17 gene transcription in coordination with RORγt and is bound by p300 (24). However, expression of Il 17f is only partially dependent on CNS2, a possible explanation for the CBP30 specificity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…CBP/p300 is thought to be involved at an early stage, consistent with our data showing key sensitivity of human IL 17A transcription to CBP/p300 inhibition (38,39). In murine Th17 cells, conserved noncoding sequence 2 (CNS2) is important to drive Il 17 gene transcription in coordination with RORγt and is bound by p300 (24). However, expression of Il 17f is only partially dependent on CNS2, a possible explanation for the CBP30 specificity.…”
Section: Discussionsupporting
confidence: 88%
“…Cytokinedriven induction of the transcriptional Th17 profile is strongly mediated by epigenetic mechanisms (23), one facilitator being the transcriptional coactivator p300. Recent studies demonstrated that p300 binds to the Il 17a promoter in murine Th17 cells and facilitates chromatin accessibility (24).…”
mentioning
confidence: 99%
“…5C). This region encompasses the conserved noncoding sequence (CNS)-2 enhancer (16). We then generated reporter constructs with a minimal proximal promoter (−301/+37) linked to different portions of this critical region.…”
Section: Irf3 Interacts With Rorγt and Limits Its Recruitment To The mentioning
confidence: 99%
“…Interestingly, multiple RORγ-binding sites were identified in the IL-17/IL-17F gene locus. To test the function of these elements in the transcriptional regulation, Wang et al [5] deleted one cis element, CNS2 in the IL-17/IL-17F gene locus and found that RORγ-dependent IL-17 transcription was almost completely suppressed. Moreover, epigenetic activation of the gene locus was affected, though how RORγ interacts with the epigenetic machineries remains unknown at this stage.…”
mentioning
confidence: 99%